Introduction. (December 2014) - Kilby, Jane; Ray, Larry
Abstract: After many decades of neglect, sociologists have in recent years been giving renewed attention to violence and the problem of how to develop theoretically informed approaches to questions of definition, understanding and explanation. This volume is part of this ongoing project, which has an urgency generated both by the reality of violence and suffering and the need to address previous lack of sociological engagement. Violence is a complex phenomenon that involves violation, trauma and loss, which requires sociologists to contemplate the antithesis of the social, which is not anything as simple as 'antisocial behaviour'. While violence is a negative phenomenon that has no obvious antonym, it is clearly part of social life, social structures and institutions. It is at times also an agent of social and political change. In many ways confrontation with violence takes sociology to its limits and as both literary writers and sociologists have claimed, the attempt to understand it will ultimately lead us into the dark. A new sociology is one committed to imaginative, innovative ways of exploring violence, with inspiration sought from cognate disciplines and from art and literature.